Highlights in the history of the American press : a book of readings - Ford, Edwin H. (Edwin Hopkins), 1891-1964; Emery, Edwin (University of Minnesota Press, 1954)
The articles collected in this volume present a vivid panorama of American journalistic history from its antecedents in the English ballad singers to the press giants of modern times. Since there is probably no single force that has played a greater role.